2015
DOI: 10.1002/anie.201408651
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐Promoted ortho‐CH Amination with Pd Catalysts

Abstract: 2,4,6-Trimethoxypyridine is identified as an efficient ligand for promoting a Pd-catalyzed ortho-C-H amination of both benzamides and triflyl-protected benzylamines. This finding provides guidance for the development of ligands that can improve or enable Pd(II)-catalyzed Csp2-H activation reactions directed by weakly coordinating functional groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 87 publications
1
52
0
Order By: Relevance
“…In pathway C, an arene C–H bond is functionalized by an electrophilic amination reagent, which may be either a nitrene source or an amine possessing a leaving group. 4 Although C–H bond coupling components are widely available, only a very limited number of electrophilic nitrogen sources are commercially accessible. Currently, most examples of C–H bond aminations feature reactivity by pathway C. Iridium, rhodium, and cobalt catalysts have been used in the amination of directing-group-containing arenes with azides, acetoxycarbamates, and dioxazolones.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In pathway C, an arene C–H bond is functionalized by an electrophilic amination reagent, which may be either a nitrene source or an amine possessing a leaving group. 4 Although C–H bond coupling components are widely available, only a very limited number of electrophilic nitrogen sources are commercially accessible. Currently, most examples of C–H bond aminations feature reactivity by pathway C. Iridium, rhodium, and cobalt catalysts have been used in the amination of directing-group-containing arenes with azides, acetoxycarbamates, and dioxazolones.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most examples of C–H bond aminations feature reactivity by pathway C. Iridium, rhodium, and cobalt catalysts have been used in the amination of directing-group-containing arenes with azides, acetoxycarbamates, and dioxazolones. 4a–d Ellman has shown that aryl azides can be reacted with imines under rhodium catalysis to afford acridines. 4e Nakamura has used an aminoquinoline directing group to couple arenes with secondary chloroamines under iron catalysis, and Miura has disclosed copper-catalyzed reactions of heterocycles with chloroamines.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations